Quantitative evaluation of hindlimb grip strength in mice as a measure of neuromuscular function - Yaochao Zheng; Alexander Lunn; Jinghui Gao; Hongyu Chen; Yao Yao (MethodsX)
Muscle strength is a crucial metric for assessing motor function, with significant diagnostic and prognostic value. It is widely used in clinical and preclinical studies as a phenotypic indicator. In mouse models of neuromuscular disorders, grip strength provides a direct, repeatable measure of motor function changes throughout disease progression. Hindlimbs are critical evaluative targets in research due to their relevancy to rodent motor functions, but assessing their strength remains a challenge. Existing methods, such as the wire-hanging test, in vivo quadriceps contractility measurements, and isolated muscle or myofiber tests, each have limitations. The wire-hanging test, though repeatable, does not explicitly isolate hindlimbs, while in vivo contractility testing requires deep anesthesia, potentially compromising accuracy. Isolated muscle tests offer precise measurements but necessitate animal sacrifice, preventing longitudinal measurements. This study introduces an optimized method for assessing hindlimb grip strength that improves consistency and accessibility. • It can be applied to measure both hindlimbs simultaneously, allowing for repeatable pre- and post-treatment comparisons. • It enables single-hindlimb evaluation, supporting self-comparisons. • This method is sensitive, user-friendly, and suitable for researchers of all expertise levels. It offers a robust tool for future research on neuromuscular interventions.